2012
DOI: 10.3390/molecules17067305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Field Water Capacity on Secondary Metabolites, Phenylalanine Ammonia-lyase (PAL), Maliondialdehyde (MDA) and Photosynthetic Responses of Malaysian Kacip Fatimah (Labisia pumila Benth)

Abstract: A randomized complete block design 2 × 4 experiment was designed and conducted for 15 weeks to characterize the relationships between production of total phenolics, flavonoid, anthocyanin, leaf gas exchange, total chlorophyll, phenylalanine ammonia-lyase (PAL) and malondialdehyde (MDA) activity in two varieties of Labisia pumila Benth, namely the var. alata and pumila, under four levels of evapotranspiration replacement (ER) (100%; well watered), (75%, moderate water stress), (50%; high water stress) and (25%;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 56 publications
7
58
0
1
Order By: Relevance
“…In our investigation, total flavonoids and anthocyanin content was found to increase in stressed plants of both black gram and green gram ( Fig. 2-C, D, E, F) which is in consistent with earlier findings (Jaafar et al, 2012;Baroowa and Gogoi, 2013). This increased level of anthocyanin contents were associated with an enhanced resistance to water loss as the glycosides attached to the anthocyanin in vacuoles adjust the osmotic potential of the cells, thereby minimizing the water loss through evapotranspiration (Chutipaijit et al, 2008).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In our investigation, total flavonoids and anthocyanin content was found to increase in stressed plants of both black gram and green gram ( Fig. 2-C, D, E, F) which is in consistent with earlier findings (Jaafar et al, 2012;Baroowa and Gogoi, 2013). This increased level of anthocyanin contents were associated with an enhanced resistance to water loss as the glycosides attached to the anthocyanin in vacuoles adjust the osmotic potential of the cells, thereby minimizing the water loss through evapotranspiration (Chutipaijit et al, 2008).…”
supporting
confidence: 81%
“…Under drought, increased production of secondary metabolites like flavonoids and phenolics is often observed in plants which is beneficial for resisting the adverse effect of drought (Jaafar et al, 2012 Santos et al, 2004). However, in most of the plant species, these biochemical and physiological modifications are not sufficient for survival when severe drought conditions remain constant over time.…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner, in stressed peas (Pisum sativum), the overall amount of anthocyanins (product of biomass and anthocyanin concentration) is about 25 % higher as in plants cultivated under standard conditions (Nogués et al 1998): although the biomass of the stressed pea plants is only about one third of the control plants, the massive increase in the concentration of phenolic compounds still resulted in a real increase of anthocyanins in the stressed plants. In the same manner, Jaafar et al (2012) reported that not only the concentration but also the overall production of total phenolics and flavonoids per plant is enhanced in plants suffering drought stress, although the explicit data on biomass per plant are not displayed by the authors. In contrast, the overall yield of flavonoids was nearly the same, when the plants were either grown under drought stress or under well-watered, non-stress conditions.…”
Section: Synthesis and Accumulation Of Natural Products Is Enhanced Imentioning
confidence: 80%
“…Furthermore, as the level of drought increases, the level of oxidative stress in the cells and tissues of plants also increased, which implies the initiation of lipid peroxidation. Therefore, the increase in antioxidant levels is attributed to its free radical scavenging capacity, which avoids lipid peroxidation, thus maintaining a cell membrane free of injury (Jaafar et al, 2012). As can be observed in Figures 1 and 2, the results of the TPC, TFC and radical scavenging activity were higher in the rhizomes than in the stems.…”
Section: Discussionmentioning
confidence: 81%